Anxiety in hospitalized children - María Castañeda, Ana (2004)
Anxiety is a feeling which can be lived intensively by children when they are exposed to under pressure situations. This research pretends to measure trait and state anxiety in hospitalized children and young people. Results show no significant differences in anxious behaviors levels of hospitalized children and young people in Cardiology, Traumatology, Gastroenterology and Dermatology services. However through the analysis of applied test items, characteristics referring anxiety as trait are found being necessary the individual considerations before the statistical one because people answer in a different way depending on their personal history, education, culture and relationship.